Development of bio fabricated gold nanoparticles for disinfectant applications in impregnated medical gloves to improve the personal protection during the nursing care. (1st October 2022) - Yan, Yuanyuan; Li, Xiaoping; Chen, Ye; Cui, Rongxia
Abstract: The present study involves the use of Gnidia glauca (G.glauca) leaf extract in the fabrication of gold nanoparticles (Au NPs), dip-coated onto the surface of gloves and their antimicrobial properties were studied for use in nursing care. The prepared Au NPs were studied by various spectroscopic and microscopic techniques. Au NPs were Purple in color with a characteristic plasmon resonance peak on the surface at a wavelength of 532 nm. The images of transmission electron microscopy (TEM) showed the Au NPs with size ranging from 22–35 nm. The crystalline size and nature of Au NPs was demonstrated by x-ray diffraction (XRD) and Energy dispersive x-ray spectroscopy (EDS) analysis. Further, antimicrobial results showed that the AuNPs-coated gloves demonstrated good antibacterial effect, notably against multidrug-resistant bacteria. Hence, the highly effective AuNPs-coated gloves may be ideal candidates for preventing or minimising indirect microbial transmission and cross-contamination in nursing care.